Negative Thermal Expansion in Ferromagnetic Fe-Ni Invar Alloys - Yusof, Hashim; Jinan Basheer, Ahmed; Ismail K., Al-Faluji (2010)
The INVAR effect in 3D-transition metal Fe1-xNix alloys with x=0.35, 0.50,0.70 is studied.Experiments have been made on thermal and structural properties to study the physical origin of INVAR characteristics such as thermal expansion atomic ordering, phase transition and curie temperature (Tc) which are closely related to its ferromagnetism. Fe0.65Ni0.35 shows an anomalously negative thermal expansion coefficient below the curie temperature 528K with Fcc structure. This behavior is not found in other combination.The specific heat results shows an anomalous temperature dependant where a strong decrease in curie temperature as well as the magnetic heat of transformation occur with decreasing Ni% content.